Elucidating the cause of variation in low‐temperature sausage protein oxidation along storage period via lipid oxidation and lipolysis. Issue 7 (25th May 2022) - Han, Hongjiao; Zhang, Zhenghan; Wang, Jianing; Liu, Dongyu; Liu, Aicheng; Song, Wanying; Zheng, Yan; Yue, Xiqing
Abstract: Protein oxidation is known to be affected by lipid oxidation and lipolysis in meat and meat products. This study aimed to determine the changes in lipid oxidation and lipolysis during low‐temperature sausage storage and to quantify their effect on protein oxidation using a mixed effects model. With prolonged storage time, the protein carbonyls, peroxide values (PVs), and thiobarbituric acid‐reactive substances (TBARS) gradually increased, along with loss in lipase activity and the accumulation of free fatty acids and neutral lipids. Both PVs and TBARS could explain a large part of the variation in protein carbonyls. Free fatty acids were significant predictors of variation in protein oxidation when they were included in a model also including storage periods. The protein carbonyls were also influenced by lipase activity, albeit indirectly. Taken together, protein oxidation, lipid oxidation, and lipolysis in low‐temperature sausage during storage were interdependence and interaction, and mutually promoted each other. Practical applications: In the meat industry, one major focus is the development of meat products that are safe and nutritious. As an alternative to traditional preparation methods, low‐temperature heating has been used in meat production, including low‐temperature sausage, to help retain nutrients and texture. The quality of low‐temperature meat products when circulated to consumers stored at room temperature is worthy of attention. However, detailed studies regarding the impact of storage time on protein oxidation, lipid oxidation, and lipolysis of low‐temperature sausage when stored at room temperature have not been reported. Our study will expand our knowledge on low‐temperature meat products, and also provide new directions for assessing the quality and safety control of meat products.